Prevalência de asma, rinite alérgica e eczema atópico nos escolares de 6 a 7 anos em Uberlândia - MG: metodologia Isaac fase 3 - Ambrósio, Melicégenes Ribeiro (2003)
In 1992, the International Study of Asthma and Allergies in Childhood (ISAAC) was created with the objective of studying the prevalence of asthma, allergic rhinitis and atopic eczema in childhood and adolescence. A standardized questionnaire was translated and validated at several countries allowing comparisons among them. The objective of this study is to know the prevalence of allergic diseases and its risk factors for childhood in Uberlândia (ISAAC phase 3), and to compare it with the data already obtained (ISAAC phase 1). It was raffled 50 representative schools of the whole city and directed the questionnaire standardized by ISAAC to the age group from 6 to 7 years. The parents or responsible person answered it. A sample of 3.108 children was obtained (58% of the questionnaires were answered). In the asthma module it was obtained: wheeze ever: 51,1%; wheeze in the last 12 months: 22,0%; 1 to 3 attacks: 18,6%; 4 to 12 attacks: 3,2%; more than 12 attacks: 0,5%; sleep disturbed by wheeze: less than 1 night a week: 10,8%, more than 1 night: 6,6%; speech limited by wheeze: 5,1%; astma ever: 5,3%; wheeze after exercises: 6,2%; dry cough during the night: 36,8%, predominant in male. It was verified sub-diagnosed asthma when the criteria of “possible asthma” (19,4%), and “probable asthma” (15,1%) were used. It was found an association between asthma reports and rhinitis, and also with atopic eczema. In the rhinitis module it was obtained: nasal symptoms without flu ever: 30,0%; nasal symptons on the last 12 months without flu: 24,4%; nasal symptoms in association with ocular symptoms: 12,6%; limited on daily activities: mild: 9,4%, moderate: 3,4%, high: 1,3%; rhinitis ever: 21,9%; months with predominantXI symptoms: may, june, july and august (winter). Rhinitis ever was predominant in male. In the eczema module it was obtained: icthy rash ever: 15,7%; icthy rash in the last 12 months: 10,7%; icthy rash in flexural areas: 6,3%; age of beginning: less than 2 years: 2,4%, between 2 and 4 years: 3,8% more than 5 years: 4,5%; clearence of the rash in the last 12 months: 74,3%; disturbance of the sleep by icthy: less than 1 night a week: 1,1%, more than 1 night: 0,8%; eczema ever: 12,3%, without sex prevalence. When compared to ISAAC’S phase I, it was verified an increase of the symptoms and worsening of the asthma, although asthma diagnosis remained constant, also an increase on rhinitis diagnosis and symptoms and that eczema diagnosis and symptons stayed constant. In relation to risk factors for asthma we found: smoking mother, family history of asthma and parents’ allergic antecedents; for rhinitis: parents with rhinitis, parents with allergic antecedents; for eczema: parents with eczema and family history of allergy. Animais at home, allergens in the bedroom and a smoking father did not constitute risk factors. On conclusion, actually it is happening an increase on the reports prevalence of some symptoms, asthma and rhinitis diagnosis, and the eczema prevalence has remained constant. The report of asthma symptoms and rhinitis in Uberlândia are above the world average, and eczema is on the same average of prevalence.